2021
DOI: 10.3390/pharmaceutics13040462
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Gold and Silver Nanoparticles on the Differentiation into Osteoclasts In Vitro

Abstract: Gold nanoparticles (GNPs) have been widely studied to inhibit differentiation into osteoclasts. However, reports of the inhibitory effects of silver nanoparticles (SNPs) during the process of differentiation into osteoclasts are rare. We compared the inhibitory effect of GNPs and SNPs during the process of differentiation into osteoclasts. Bone marrow-derived cells were differentiated into osteoclasts by the receptor activator of the nuclear factor-kappa-Β ligand (RANKL). The inhibitory effect of GNPs or SNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Therefore, AuNPs can inhibit angiogenic activity, inhibit inflammation, or act as antioxidants, to protect cartilage tissue in arthritis. Studies have shown that AuNPs have the ability to inhibit osteoclasts and are one of the most effective nanoparticles for the treatment of bone tissue diseases [ 7 , 39 ].…”
Section: Bone Cartilage Disordermentioning
confidence: 99%
“…Therefore, AuNPs can inhibit angiogenic activity, inhibit inflammation, or act as antioxidants, to protect cartilage tissue in arthritis. Studies have shown that AuNPs have the ability to inhibit osteoclasts and are one of the most effective nanoparticles for the treatment of bone tissue diseases [ 7 , 39 ].…”
Section: Bone Cartilage Disordermentioning
confidence: 99%
“…The nGNP was prepared as previously described. 22 , 23 Detailed descriptions of the synthesis methods are provided in the Supporting Information S1 . The pGNP was prepared as described.…”
Section: Methodsmentioning
confidence: 99%
“…The DPBS was replaced with fresh DPBS. The Beer–Lambert law is used to calculate the molar concentrations of the released GNP-UDCA from the CHA-GNP-UDCA gels. , …”
Section: Materials and Methodsmentioning
confidence: 99%
“…The Beer−Lambert law is used to calculate the molar concentrations of the released GNP-UDCA from the CHA-GNP-UDCA gels. 34,35 Cell Culture for PC12 and BMMs. PC12 cells were provided by American Type Culture Collection (ATCC, Manassas, VA, USA).…”
Section: ■ Introductionmentioning
confidence: 99%